The judicial role in protecting democracy from populism. Issue 2 (25th April 2019) - Prendergast, David
Abstract: Populist political movements claim to be democratic in expressing what the people want, against the political establishment. These claims are misconceived to begin with in presupposing a definitive unitary people. Nonetheless, constitutional democracies face a special challenge to resist these claims in principle because they are unmistakably democratic sounding claims; they purport to empower popular will so that the people can rule themselves. Populist movements can be successful at the ballot box and push political culture in antidemocratic directions through democratic means, all the while claiming democratic legitimacy. The very processes of democracy are under threat. Traditionally, political winners are not motivated to change the system that saw them elected; populists are different in this regard. The populist challenge prompts a revisit of the debate about the democratic legitimacy of judges being empowered to displace the decisions of elected legislative assemblies (the constitutional review debate). An underdeveloped aspect of the constitutional review debate was the scope for courts to intervene specifically in political processes to correct them when they have gone awry and to help prevent them going awry in the first place. Judicial intervention is costly in democratic terms, and yet democracy has to be protected. This Article analyzes the search for a balance between popular will shaping democratic processes and judicially managed constitutional limitations on popular will shaping those processes. The recommended judicial role is styled as courts protecting—not perfecting—democracy, and it is a John Hart Ely-inspired modification of a separation of powers defense of constitutional review. In addressing the populist challenge, courts can, in principle, try to be a step ahead in anticipating and, where they can, slowing degradation of democracy and thereby helping to prevent it.